A CoS x PANI / MF Composite Flexible Electrode, Its Preparation Method and Application

CN117936286BActive Publication Date: 2026-11-03NINGBO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410114282.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-28
Publication Date
2026-11-03
Estimated Expiration
2044-01-28

AI Technical Summary

Technical Problem

In the prior art, the non-conductive nature of commercial low-cost polymer foams such as melamine foam (MF) limits their application in flexible supercapacitors, and cobalt sulfide nanoparticles are prone to agglomeration in practical applications, which reduces the utilization rate of active materials and cycle stability.

Method used

Polyaniline (PANI) was used to improve the conductivity of MF, and the number and dispersion of active sites were increased by constructing a hollow nanosheet array derived from the zeolite imidazole ester framework Co-ZIF-L on a flexible substrate, thus forming a CoSx/PANI/MF composite flexible electrode.

Benefits of technology

It significantly improves the electrochemical performance of flexible supercapacitors, including high specific capacitance and good cycle stability, especially maintaining good performance under high current density and multiple folding conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117936286B_ABST
    Figure CN117936286B_ABST
Patent Text Reader

Abstract

The application provides a CoS x The application provides a preparation method of a CoS / PANI / MF composite flexible electrode, which comprises the following steps: firstly, mixing an aniline solution and an ammonium persulfate solution, adding melamine foam to carry out polymerization reaction to obtain PANI / MF; then mixing a cobalt salt, a 2-methyl imidazole ligand and deionized water, and then immersing the mixture into the PANI / MF to grow a zeolite imidazole framework Co-ZIF-L nanosheet array on a substrate; finally, adding the nanosheet array into a sulfur source solution to carry out sulfuration to obtain the CoS x / PANI / MF composite flexible electrode. The application uses low-cost commercial melamine foam as a flexible substrate, uses PANI modification and hollow structure construction to increase the number of active sites, conductivity and stability of the material, and thus improves the performance of the flexible supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrode material technology, and specifically relates to CoS. x / PANI / MF composite flexible electrode. Background Technology

[0002] In recent years, with the rapid development of portable electronic devices and wearable electronic products, there is an urgent need to develop lightweight, stable, and safe flexible energy storage devices. Supercapacitors have attracted widespread attention due to their advantages such as ultra-high power density, fast charging and discharging, environmental friendliness, and long cycle life. Electrode materials are one of the main factors restricting the performance of supercapacitors, and the development of low-cost, high-performance electrodes is considered key to realizing the practical application of flexible supercapacitors.

[0003] Commercially available low-cost polymer foams, such as melamine foam (MF), possess low density, high porosity, and excellent mechanical properties, making them ideal substrate materials for the large-scale production of flexible electrodes. However, due to the non-conductive nature of MF, few electrode materials are based on it. Cobalt sulfide is one of the most widely studied electrode active materials; however, cobalt sulfide nanoparticles are prone to agglomeration during practical applications, thus reducing the utilization rate and cycling stability of the active material. Directly constructing cobalt sulfide nanosheet arrays on a flexible substrate can fully expose active sites, reduce agglomeration, and enhance conductivity. This invention introduces polyaniline (PANI) to improve the conductivity of MF; and utilizes a hollow nanosheet array derived from a zeolite imidazole ester framework (Co-ZIF-L) to increase the number and dispersion of reactive sites, thereby improving capacity, rate performance, and cycling stability. Therefore, it has promising applications in flexible supercapacitors. Summary of the Invention

[0004] The purpose of this invention is to provide a CoS x Preparation of / PANI / MF composite flexible electrode, using this method to obtain CoS x The PANI / MF composite flexible electrode has the advantage of significantly improving electrochemical performance.

[0005] The technical solution of this invention is: CoS x The method for preparing the PANI / MF composite flexible electrode is characterized by including the following steps:

[0006] (1) Dissolve aniline in 20 mL of 1 M hydrochloric acid to obtain solution A, dissolve ammonium persulfate (APS) in 20 mL of 1 M hydrochloric acid to obtain solution B, then mix solution A and solution B, add a clean piece of melamine foam (MF) to the mixed solution, and polymerize under ice bath conditions at 5 °C. Finally, remove, wash and dry to obtain PANI / MF.

[0007] (2) Dissolve cobalt salt and 2-methylimidazole in 40 mL of deionized water, then mix the solutions, add the PANI / MF prepared in step (1), stir rapidly for 5 minutes, let the solution stand at room temperature, wash and dry to obtain Co-ZIF-L / PANI / MF;

[0008] (3) Dissolve the sulfur source in anhydrous ethanol, add the Co-ZIF-L / PANI / MF prepared in step (2), and after the sulfidation reaction, wash and dry to obtain CoS. x / PANI / MF composite flexible electrode.

[0009] In step (1), the volume of aniline is preferably 20-200 μL.

[0010] In step (1), the amount of ammonium persulfate (APS) is preferably 0.05-0.15g.

[0011] In step (1), the polymerization reaction time is preferably 5-24 hours.

[0012] In step (2), the type of cobalt salt is not limited, including one or more of cobalt chloride, cobalt sulfate, and cobalt nitrate.

[0013] In step (2), the molar concentration of cobalt salt is preferably 0.02-0.15 mol / L, and the molar concentration of 2-methylimidazole is preferably 0.10-0.40 mol / L.

[0014] In step (2), the preferred molar ratio of cobalt salt to 2-methylimidazole is 1:(2-16).

[0015] In step (2), the preferred time for standing at room temperature is 2-24 hours.

[0016] In step (3), the sulfur source includes, but is not limited to, sodium sulfide, thiourea, thioacetamide or one or more, preferably thioacetamide.

[0017] In step (3), the preferred molar concentration of the sulfur source is 0.05-0.15 mol / L.

[0018] In step (3), the temperature of the sulfidation reaction is preferably 95-160℃; the reaction time is preferably 4-24 hours.

[0019] In summary, the CoS of this invention x The PANI / MF composite flexible electrode has the following beneficial effects:

[0020] (1) Using commercial melamine foam (MF) as a flexible substrate, which is low in cost, the introduction of polyaniline (PANI) improves the electron transport capability between the active material and the substrate. A cobalt-based zeolite imidazole ester framework (Co-ZIF-L) array is grown and assembled on it, and converted into cobalt sulfide nanosheets by solution sulfidation. The advantages of ZIF material, such as porous morphology and multiple active sites, are retained, which improves the specific capacity and cycle stability of the material.

[0021] (2) In a 1M KOH electrolyte solution, at a current density of 1 A / g, CoS x The / PANI / MF exhibits a high specific capacitance of 634.0 C / g. After 5000 cycles at a current density of 10 A / g, the specific capacitance retention rate is 90.2%. Furthermore, after 100 90-degree folds of the electrode, the specific capacitance retention rate is 76.2%, demonstrating excellent cycle stability and flexibility, which is of particular significance for flexible supercapacitors.

[0022] (3) The preparation method of the present invention is simple and efficient, showing a positive impact on the construction of flexible electrode materials, and can be easily extended to construct other composite flexible electrode materials for energy storage and conversion devices. Attached Figure Description

[0023] Figure 1 It is the CoS prepared in Example 1 of this invention. x Photograph of the PANI / MF composite flexible electrode;

[0024] Figure 2 It is the CoS prepared in Example 1 of this invention. x Scanning electron microscope image of the PANI / MF composite flexible electrode;

[0025] Figure 3 It is the CoS prepared in Example 1 of this invention. x Transmission electron microscopy image of the PANI / MF composite flexible electrode;

[0026] Figure 4 CoS prepared in Example 1 of this invention x Electrochemical performance of the PANI / MF composite flexible electrode in 1M KOH electrolyte solution: the left figure is the cyclic voltammetry curve at different scan rates, and the right figure is the charge-discharge curve at different current densities.

[0027] Figure 5 It is the PANI / MF and CoS prepared in Example 1 of this invention. x / PANI / MF composite flexible electrode and CoS prepared in comparison x / MF specific capacity at different current densities in 1M KOH electrolyte solution;

[0028] Figure 6 This is the CoS prepared in Example 1 of the present invention. x / PANI / MF composite flexible electrode and CoS prepared in comparison x The graph shows the cycling stability test results of / MF in 1M KOH electrolyte solution at a current density of 10A / g;

[0029] Figure 7 This is the CoS prepared in Example 1 of the present invention. x The specific capacity retention of the / PANI / MF composite flexible electrode at different folding times in 1M KOH electrolyte solution. Detailed Implementation

[0030] The preferred embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples.

[0031] Example 1:

[0032] (1) Dissolve 54.7 μL of aniline in 20 mL of 1 M hydrochloric acid to obtain solution A. Dissolve 0.0685 g of ammonium persulfate (APS) in 20 mL of 1 M hydrochloric acid to obtain solution B. Then mix solution A and solution B. Add a clean piece of melamine foam (MF) to the mixed solution. Polymerize under ice bath conditions at 5 °C for 10 hours. Finally, remove, wash and dry to obtain PANI / MF.

[0033] (2) Dissolve 0.58g cobalt nitrate hexahydrate and 1.31g 2-methylimidazole in 40mL of deionized water, then mix the solutions, add the PANI / MF prepared in step (1), stir rapidly for 5 minutes, let the solution stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L / PANI / MF;

[0034] (3) Dissolve 0.15 g of thioacetamide in 40 mL of anhydrous ethanol, add the Co-ZIF-L / PANI / MF prepared in step (2), and perform a sulfurization reaction at 120 °C for 6 hours. Wash and dry to obtain CoS x / PANI / MF composite flexible electrode.

[0035] Preparation of CoS x Photo of the PANI / MF composite flexible electrode is shown below. Figure 1 As shown, it exhibits good flexibility;

[0036] Preparation of CoS x Scanning electron microscope image of the / PANI / MF composite flexible electrode is shown below. Figure 2 As shown, it presents a nanosheet array structure;

[0037] Preparation of CoS xTransmission electron microscopy image of the / PANI / MF composite flexible electrode is shown below. Figure 3 As shown, it exhibits a hollow nanosheet structure;

[0038] The CoS obtained by the above steps x The cyclic voltammetry curves of the PANI / MF composite flexible electrode as a supercapacitor electrode material in 1M KOH electrolyte solution at different scan rates are shown below. Figure 4 As shown in the left figure; the galvanostatic discharge curves at different current densities in 1M KOH electrolyte solution, as follows. Figure 4 As shown in the right figure;

[0039] The PANI / MF and CoS obtained by the above steps x / PANI / MF and CoS prepared in comparison x / MF was used as an electrode material for supercapacitors, and its specific capacitance was tested in 1M KOH electrolyte solution at different current densities. Figure 5 As shown, at a current density of 1 A / g, CoS x / PANI / MF has a specific capacity of 630.4 C / g, which is far superior to PANI / MF and CoS. x / MF;

[0040] The CoS obtained by the above steps x / PANI / MF and CoS prepared in the comparative example x / MF, as an electrode material for supercapacitors, was tested for cycle stability in 1M KOH electrolyte solution at a current density of 10 A / g. Figure 6 As shown, after 5000 cycles, CoS x The specific capacitance retention rate of / PANI / MF is 90.2%, demonstrating good cycling stability;

[0041] The CoS obtained by the above steps x / PANI / MF was used as an electrode material for supercapacitors, and the specific capacitance retention rate under different folding times was tested in 1M KOH electrolyte solution. Figure 7 As shown, after 100 folds, CoS x The specific capacitance retention rate of / PANI / MF is 76.2%, demonstrating good stability;

[0042] Example 2:

[0043] (1) Dissolve 110.5 μL of aniline in 20 mL of 1 M hydrochloric acid to obtain solution A. Dissolve 0.135 g of ammonium persulfate (APS) in 20 mL of 1 M hydrochloric acid to obtain solution B. Then mix solution A and solution B. Add a clean piece of melamine foam (MF) to the mixed solution. Polymerize under ice bath conditions at 5 °C for 12 hours. Finally, remove, wash and dry to obtain PANI / MF.

[0044] (2) Dissolve 0.58g cobalt nitrate hexahydrate and 1.31g 2-methylimidazole in 40mL of deionized water, then mix the solutions, add the PANI / MF prepared in step (1), stir rapidly for 5 minutes, let the solution stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L / PANI / MF;

[0045] (3) Dissolve 0.15 g of thioacetamide in 40 mL of anhydrous ethanol, add the Co-ZIF-L / PANI / MF prepared in step (2), and perform a sulfurization reaction at 120 °C for 6 hours. Wash and dry to obtain CoS x / PANI / MF composite flexible electrode.

[0046] The CoS obtained by the above steps x / PANI / MF was used as an electrode material for supercapacitors. The specific capacity of the electrode was tested at different current densities in 1M KOH electrolyte solution. The electrode had a specific capacity of 598.5 C / g at a current density of 1 A / g.

[0047] Example 3:

[0048] (1) Dissolve 54.7 μL of aniline in 20 mL of 1 M hydrochloric acid to obtain solution A. Dissolve 0.0685 g of ammonium persulfate (APS) in 20 mL of 1 M hydrochloric acid to obtain solution B. Then mix solution A and solution B. Add a clean piece of melamine foam (MF) to the mixed solution. Polymerize under ice bath conditions at 5 °C for 10 hours. Finally, remove, wash and dry to obtain PANI / MF.

[0049] (2) Dissolve 0.29g cobalt nitrate hexahydrate and 1.31g 2-methylimidazole in 40mL of deionized water, then mix the solutions, add the PANI / MF prepared in step (1), stir rapidly for 5 minutes, let the solution stand at room temperature for 8 hours, wash and dry to obtain Co-ZIF-L / PANI / MF;

[0050] (3) Dissolve 0.15g of thioacetamide in 40mL of anhydrous ethanol, add the Co-ZIF-L / PANI / MF prepared in step (2), and perform a sulfurization reaction at 120℃ for 6 hours. Wash and dry to obtain the CoSx / PANI / MF composite flexible electrode.

[0051] The CoS obtained by the above steps x / PANI / MF was used as an electrode material for supercapacitors. The specific capacitance of the electrode was tested at different current densities in 1M KOH electrolyte solution. The electrode showed a specific capacitance of 605 C / g at a current density of 1 A / g.

[0052] Example 4:

[0053] (1) Dissolve 54.7 μL of aniline in 20 mL of 1 M hydrochloric acid to obtain solution A. Dissolve 0.0685 g of ammonium persulfate (APS) in 20 mL of 1 M hydrochloric acid to obtain solution B. Then mix solution A and solution B. Add a clean piece of melamine foam (MF) to the mixed solution. Polymerize under ice bath conditions at 5 °C for 10 hours. Finally, remove, wash and dry to obtain PANI / MF.

[0054] (2) Dissolve 0.58g cobalt nitrate hexahydrate and 1.31g 2-methylimidazole in 40mL of deionized water, then mix the solutions, add the PANI / MF prepared in step (1), stir rapidly for 5 minutes, let the solution stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L / PANI / MF;

[0055] (3) Dissolve 0.25g of thiourea in 40mL of anhydrous ethanol, add the Co-ZIF-L / PANI / MF prepared in step (2), and perform a sulfurization reaction at 130℃ for 8 hours. Wash and dry to obtain the CoSx / PANI / MF composite flexible electrode.

[0056] The CoS obtained by the above steps x / PANI / MF was used as an electrode material for supercapacitors. The specific capacity of the electrode was tested at different current densities in 1M KOH electrolyte solution. The electrode had a specific capacity of 610.2 C / g at a current density of 1 A / g.

[0057] Comparative example:

[0058] (1) Dissolve 0.58g cobalt nitrate hexahydrate and 1.31g 2-methylimidazole in 40mL of deionized water, then mix the solutions, add a clean piece of melamine foam (MF), stir rapidly for 5 minutes, let the solution stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L / MF;

[0059] (2) Dissolve 0.15 g of thioacetamide in 40 mL of anhydrous ethanol, add the Co-ZIF-L / MF prepared in step (1), and perform a sulfurization reaction at 120 °C for 6 hours. Wash and dry to obtain CoS x / MF.

[0060] The CoS obtained by the above steps x / MF was used as an electrode material for supercapacitors, and its specific capacitance was tested in 1M KOH electrolyte solution at different current densities. Figure 5 As shown, at a current density of 1 A / g, CoS x / MF has a specific capacity of 190.2 C / g.

[0061] The embodiments described above are detailed descriptions of the technical solutions of the present invention and should be understood as specific implementation measures of the present invention. They are not intended to summarize the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention shall fall within the scope of protection that the present invention should enjoy.

Claims

1. A CoS x The method for preparing the PANI / MF composite flexible electrode is characterized by including the following steps: (1) Dissolve 54.7 μL of aniline in 20 mL of 1 M hydrochloric acid to obtain solution A. Dissolve 0.0685 g of ammonium persulfate (APS) in 20 mL of 1 M hydrochloric acid to obtain solution B. Then mix solution A and solution B, add a clean piece of melamine foam (MF), and polymerize under ice bath conditions at 5 °C for 10 hours. Finally, remove, wash and dry to obtain PANI / MF. (2) Dissolve 0.58g cobalt nitrate hexahydrate and 1.31g 2-methylimidazole in 40mL of deionized water, then mix the solutions, add the PANI / MF prepared in step (1), stir rapidly for 5 minutes, let the solution stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L / PANI / MF; (3) Dissolve 0.15 g of thioacetamide in 40 mL of anhydrous ethanol, add the Co-ZIF-L / PANI / MF prepared in step (2), and perform a sulfurization reaction at 120 °C for 6 hours. Wash and dry to obtain CoS x / PANI / MF composite flexible electrode.

2. CoS obtained by the preparation method according to claim 1 x Applications of the PANI / MF composite flexible electrode as an electrode for flexible supercapacitors.

Citation Information

Patent Citations

  • Method for preparing foamy carbon-based flexible electrode material based on supercritical fluid technology

    CN112002563A

  • Preparation method of PANI array / CuS (at) fCC composite electrode material

    CN114496593A